Penerapan Sistem Informasi Akuntansi Terhadap Transaksi Bisnis Perusahaan - Lenny Widiawati; Agus Munandar (Cakrawala Repositori IMWI, 2023)
This study aims to determine the application of accounting information systems to business transactions at a motorcycle sales and service company. The method used in this research is qualitative where the data collection is obtained through interviews, documentations, and observations. Based on research conducted, the use of this information system is very helpful for companies in carrying out business transactions so that they are more effective and efficient. In addition, an unstable internet network is one of the obstacles that hinder the process of recording transactions.